2021
DOI: 10.2174/0929867328666210218182203
|View full text |Cite
|
Sign up to set email alerts
|

Viral Envelope Membrane: A Special Entry Pathway and a Promising Drug Target

Abstract: Enveloped viruses belong to a large class of pathogens responsible for multiple serious diseases. Their spread into new territories has been the cause of major epidemics throughout human history, including the Spanish flu in 1918 and the latest COVID-19 pandemic. Thanks to their outer membrane, consisting essentially of host lipids, enveloped viruses are more resistant to enzymes, and are also less susceptible to host immune defenses than their naked counterparts. Therefore, the development of effective approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Additionally, targeting the viral envelope is attractive due to the anticipated rate of resistance development being negligible. The viral lipid envelope originates from the host cell’s membrane and is thus not affected by natural viral diversity and variability [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, targeting the viral envelope is attractive due to the anticipated rate of resistance development being negligible. The viral lipid envelope originates from the host cell’s membrane and is thus not affected by natural viral diversity and variability [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…The localization of our PN19 peptide and its ability to bind MPER derived peptide could indicate a different mechanism of inhibitory activity. Molecular evidence showed that juxtaposition of the S2 IFP and MPER domains facilitates the formation of the fusion pore through lipid destabilization in the late steps of viral cell membrane fusion ( Behzadipour and Hemmati, 2022 ; Palombi et al., 2021 ; Santamaria et al., 2022 ; Mahajan and Bhattacharjya, 2015 ). Thus, the interaction between the IFP and the MPER in membrane context would be one of the most important targets where peptide PN19 exerted its mechanism of action.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, indirect-acting antivirals (IAAs) inhibit the host’s proteins, with the advantage of reducing the viral resistance associated with viral high mutation rates . A large number of host proteins are implicated in viral replication for entry, genome replication, and host immune signaling . DEAD-box helicases are a large family of human proteins involved in cell cycle control, immune system, and all aspects of RNA metabolism, including ribosome biogenesis, translation, and decay .…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, human proteins possess DNA-repair enzymes able to minimize the number of mutations. Accordingly, some host directed antivirals (HDAs) have been designed in recent years, targeting human proteins involved in immune signaling pathways or in viral replication processes like translation or cell traffic . A successful example on this regard is represented by maraviroc which binds human chemokine receptor CCR5, preventing HIV-1 entry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation